ByzRev 02.2020.023: Ken Dark – Jan Kostenec, Hagia Sophia in Context. An Archaeological Re-Examination of the Cathedral of Byzantine Constantinople.: Oxford – Havertown, PA: Oxbow Books 2019. - Efthymiadis, Stephanos (The Byzantine Review, 2020)
Ken Dark – Jan Kostenec, Hagia Sophia in Context. An Archaeological Re-Examination of the Cathedral of Byzantine Constantinople. Oxford – Havertown, PA: Oxbow Books 2019. X, 141 pp. – ISBN 978-1-78925-030-5 (£55.00)